Megalithic Culture In Kandangan Site Senduro Sub-District Lumajang District - Amelia, Si'ta Fanimatul; Swastika, Kayan; Na’im, Mohamad; Sumarjono, Sumarjono; Pratama, Akhmad Ryan; Jamil, Robit Nurul (History Education, University of Jember, 2022)
Megalithic culture is a global phenomenon in the history of human culture. The remains of megalithic culture are almost scattered in various regions in Indonesia, one of which is in Lumajang Regency. Lumajang Regency, almost all of its sub- districts have artifacts or findings in the form of artifacts and texts from prehistoric times to the present. Prehistoric relics are found in Lumajang, one of which is in Kandangan Village. The purpose of this study was to inventory the archaeological remains in Kandangan Village. The method used in this research is the historical method. The results of this study are an inventory of the number, distribution, typology, and the belief system adopted, namely the belief in ancestors, with the social, cultural, and economic life of the megalithic culture supporting community at Kandangan Site which has a conception of being interrelated with one another. Keywords: Culture, Kandangan Site, Megalithic.